The role of trimethylamine-N-oxide level in the diagnosis of diabetic retinopathy and the differential diagnosis of diabetic and nondiabetic retinopathy - Yakar, Burkay; Onalan, Erhan; Kaymaz, Tugce; Donder, Emir; Gursu, Mehmet Ferit (Consel Brasil Oftalmologia, 2024)
Purpose: Trimethylamine N-oxide serum levels have been associated with type 2 diabetes mellitus and its complications. The current study aimed to find out if plasma trimethylamine N-oxide level may be a novel marker in the diagnosis of diabetic retinopathy and if it can be used in the differential diagnosis of diabetic and nondiabetic retinopathy. Methods: The study included 30 patients with diabetic retinopathy, 30 patients with nondiabetic retinopathy, 30 patients with type 2 diabetes mellitus without retinopathy, and 30 healthy control participants. Biochemical parameters, serum IL-6, TNF-alpha, and trimethylamine N-oxide levels were measured in all participants. Results: Trimethylamine N-oxide level was significantly higher in diabetic retinopathy than in the other groups (p<0.001). There was no significant difference in trimethylamine N-oxide levels between nondiabetic retinopathy and control or type 2 diabetes mellitus Groups. There was a significant positive correlation between trimethylamine N-oxide level and elevated FPG, BMI, HOMA-IR score, BUN, IL-6, and TNF-alpha levels. Conclusion: The current study showed that the trimethylamine N-oxide level is elevated in diabetic retinopathy. These findings suggest that serum trimethylamine N-oxide level might be a novel marker for diabetic retinopathy, and it might be used in the differential diagnosis of diabetic and nondiabetic retinopathy.
Papel do nível de N-óxido de trimetilamina no diagnóstico da retinopatia diabética e no diagnóstico diferencial da retinopatia diabética e não-diabética
Keywords: Biomarkers; Diabetic retinopathy; Differential diag-nosis; Oxides; Type 2 diabetes mellitus; Trimethylamine-N-oxide; Trimethyloxamine